Outcomes of Uncemented Bipolar Hemiarthroplasty for Femoral Neck Fractures in Elderly Patients with Cardiac Dysfunction - Usman Zafar Dar, Ali Muqaddas, Mohammad Nauman Shahid, Sameer Ahmed, Muhammad Ahmed, Naeem Hussain (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: Cementless hemiarthroplasty is advised because it reduces the risk of morbidity and mortality in older individuals who use cement. For older patients with high-risk clinical issues who had femoral neck fractures, we assessed the effectiveness of cementless hemiarthroplasty. Materials and Methods: The design of this study was a cross sectional study design and this study was conducted in DHQ Teaching Hospital Gujranwala. 48 patients, including 19 male and 29 female, with an average age of 88-years. using cementless hemiarthroplasty to treat patients with femoral neck fractures. 30 patients (62%) had porous-coated femoral stems, while 18 patients had modular femoral revision stems (38 percent). All patients had bipolar femoral heads. Following surgery, the follow-up radiologically was performed at yearly intervals. Results: The average number of followup years was 4.2. There were no hospital-related deaths among the patients. Six patients (12%) experienced medical difficulties during the period of follow-up, and 4-patients (8%) passed away. Due to acetabular degradation, only the 2 hips were changed to the total hip replacements. One patient was scheduled for a femoral revision due to a sinking of greater than 3 mm. No patients developed heterotopic ossification or acetabular protrusion. The HHA (Harris-hip average) score is 84. One patient experienced dislocation (2 percent). Practical Implication: The advantages of the cemented technique seem to be offset by its mortality risk and the advantages of the cementless option by its increased morbidity. Thus, in some of these very elderly morbid patients the orthopedic surgeon is faced with a dilemma regarding the correct surgical choice, which should be one that can promise pain relief and rapid resumption of function and, at the same time, prevent mortality and reduce morbidity Conclusion: An appropriate form of therapy for fractures in femoral neck in older individuals with risk of clinical issues, particularly those of the cardiopulmonary character, is cementless hemiarthroplasty. With this technique, after cemented hemi-arthroplasty the risk of fat embolism and hypotension is reduced. Keywords: Uncemented Bipolar Hemiarthroplasty, Uncemented Femoral Prosthesis, Hemiarthroplasty In Elderly, Cardiac Dysfunction, Femoral Neck Fracture.